CONCEPT AND LEGAL FOUNDATIONS OF OPERATIONAL SEARCH ACTIVITY - D.I. Toshtemirov (Scholar Express Journals, 2025)
This article provides a scientific analysis of the legal nature of operational search activities, their role in combating crime, and their significance in ensuring the rights and freedoms of citizens. The implementation of operational search activities by specially authorized bodies in strict compliance with legality, law and order, and state interests further strengthens their position in the law enforcement system
Keywords: Operational Search Activity; Operational Search Measures; Combating Crime